Heraclitus and the Path to our Interior Aspect (2023)
There are elements in Heraclitus that are enticing to modern readers in that they point toward a certain intimacy of consciousness. Having read the fragments of this philosopher, we propose a reading that harmonizes his assertions about universality with his assertions about self-knowledge, in which we believe we can glimpse the discovery of self-awareness. In Heraclitus’ view, humans possess a soul with an unlimited horizon and a capacity to access the logos. A person must pursue introspection, listen to the logos, and find the unity of all things and himself. This will enable us to gain a deeper understanding of the interiority of self-awareness without sacrificing its connection to the universal. Furthermore, individuals must speak the logos to themselves to act according to it. By acting otherwise, one would be acting against his own inner self.